Gait among patients with myotonic dystrophy type 1: A three-dimensional motion analysis study - Vincent Tiffreau; Christine Detrembleur; Peter Van Den Bergh; Anne Renders; Virginie Kinet; André Thevenon; Etienne Allart; Thierry Lejeune (The Journal of the International Society of Physical and Rehabilitation Medicine, 2018)
Objective: The objective was to characterize the gait abnormalities in myotonic dystrophy type 1 patients. Material and Methods: Outcomes variables were kinematic and kinetic parameters, timing of muscles, mechanical work and energy cost, and the motor function measure. Results: Despite a high cadence and a low ankle range of motion ratio, ankle extension power, and first extension moment of the knee during the stance, the mechanical work and energy cost were normal. The duration of electromyography activation of the gastrocnemius lateralis (GL) muscle was abnormally long. Conclusion: The hypothesis of a myotonic activity of the GL during the swing phase should be investigated.